Meat intake is associated with a higher risk of ulcerative colitis in a large European prospective cohort studyø - Dong, C; Chan, SSM; Jantchou, P; Tong, YNT (Oxford University Press, 2022)
Background and Aims We aimed to investigate the association between protein intake and risk of inflammatory bowel disease [IBD] in the European Prospective Investigation into Cancer and Nutrition.